Implementation of Web-Based Loan Application Information System Using Simple Additive Weighting (SAW) at CV. Taruna Jaya Nusantara - Tambunan, William Jeans; Darusalam, Ucuk; Nugroho, Catur (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Financial institutions offer cash loans with lighter terms and collateral compared to banks, including motor vehicle ownership as collateral. This study focuses on implementing a web-based Loan Application Information System using the Simple Additive Weighting (SAW) method at CV. Taruna Jaya Nusantara. The research aims to enhance the efficiency of the loan application process and evaluate loan feasibility. The system development method is integrated with web technology, with SAW used to measure relevant criteria. Implementing the Loan Application Information System with SAW significantly simplifies decision-making, reduces potential errors, and improves loan feasibility evaluation. Based on the ranking results, V1 = 1.9; V2 = 1.779; V3 = 2.0625. The selection process uses a tolerance limit for acceptance, where the accepted value threshold is set at > 2. Thus, it can be concluded that A3 with a value of 2.0625 meets the criteria for recommendation.